Edukasi Pengobatan Tradisional Dan Modern Schistosomiasis Di Desa Langko, Kecamatan Lindu - Tandi, Joni; Handayani, Tien Wahyu; Arynesta, Teddy; Andini, Tuti Allawiah; Insani, Nabila Nurul; Gintu, Tri Juniver (Yumary: Jurnal Pengabdian kepada Masyarakat, 2025)
Purpose: To provide new knowledge to the Langko Village community about schistosomiasis, which can be treated with synthetic drugs such as praziquantel and anthelmintics, and traditional medicine using betel nuts. Methodology/approach: The PKM activity in Langko Village was carried out in three stages, namely preparation including a location survey to obtain permission from local government officials and prepare the necessary facilities and infrastructure needed during the activity, the second stage is providing education through lectures and material brochures, discussions, and measuring the level of community satisfaction with the activities carried out through activity evaluation by distributing questionnaires, and the third stage is distributing assistance to the community present in the form of basic necessities. Results: The community was very satisfied with this educational activity, with an average satisfaction value of 98% from six satisfaction assessment indicators. Conclusions: The community health education program successfully enhanced local knowledge of schistosomiasis treatment options, demonstrating high community acceptance of both conventional pharmaceutical interventions and traditional betel nut therapy. Limitations: The limitations of this PKM activity have not been able to reach all the snail focus areas because road access is still damaged. Contribution: This PKM has significant implications for public health in Langko Village, where partners feel helped by the new knowledge, namely, betel nut as a medicine for schistosomiasis, which is far from side effects compared to chemical drugs.